If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-3k + 8) = -6k + 2(5k + 8) Reorder the terms: 4(8 + -3k) = -6k + 2(5k + 8) (8 * 4 + -3k * 4) = -6k + 2(5k + 8) (32 + -12k) = -6k + 2(5k + 8) Reorder the terms: 32 + -12k = -6k + 2(8 + 5k) 32 + -12k = -6k + (8 * 2 + 5k * 2) 32 + -12k = -6k + (16 + 10k) Reorder the terms: 32 + -12k = 16 + -6k + 10k Combine like terms: -6k + 10k = 4k 32 + -12k = 16 + 4k Solving 32 + -12k = 16 + 4k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-4k' to each side of the equation. 32 + -12k + -4k = 16 + 4k + -4k Combine like terms: -12k + -4k = -16k 32 + -16k = 16 + 4k + -4k Combine like terms: 4k + -4k = 0 32 + -16k = 16 + 0 32 + -16k = 16 Add '-32' to each side of the equation. 32 + -32 + -16k = 16 + -32 Combine like terms: 32 + -32 = 0 0 + -16k = 16 + -32 -16k = 16 + -32 Combine like terms: 16 + -32 = -16 -16k = -16 Divide each side by '-16'. k = 1 Simplifying k = 1
| Ix-4I=-3 | | 3n+6=16 | | F(x)=cos(pi+x) | | 3y+2=7y+10 | | g(z)=Cos(pi+g) | | 4y+2x=13.50 | | .77=In(y) | | 46=-5(m+3)-7(m-7) | | 0.77=ln(y) | | 0.5x-4=7-x | | 7+2[a-3]=-9 | | -8a+15=-105 | | 4x+2y=13.50 | | H-(-7)=12 | | 4x+2x=13.50 | | -6(a+8)+6(1-8)=-78 | | 7x-5=5x+8 | | -7x-4-4x=9x+4x | | (x^2+10+25)-5=25 | | 2[a-4]+15=13 | | 1x^2=0 | | 5x+2x-5=30 | | 10+3x-4=18 | | 4[2a+2]-17=15 | | .2(y+3)+3=.1(7y-4)-5 | | 6+6x=1+x | | 5x-9y-11x-y= | | 5[3x+12]=-15 | | -15=-20y | | 3[t-12]=27 | | -4x+3[2x-5]=31 | | 62=3(-6+6a)+4(a-2) |